A Theoretical Model for Calculating Voltage Sensitivity of Ion Channels and the Application on Kv1.2 Potassium Channel - Yang, Huaiyu (The Biophysical Society, 2012)
Voltage sensing confers conversion of a change in membrane potential to signaling activities underlying the physiological processes. For an ion channel, voltage sensitivity is usually experimentally measured by fitting electrophysiological data to Boltzmann distributions. In our study, a two-state model of the ion channel and equilibrium statistical mechanics principle were used to test the hypothesis of empirically calculating the overall voltage sensitivity of an ion channel on the basis of its closed and open conformations, and determine the contribution of individual residues to the voltage sensing. We examined the theoretical paradigm by performing experimental measurements with Kv1.2 channel and a series of mutants. The correlation between the calculated values and the experimental values is at respective level, R(2) = 0.73. Our report therefore provides in silico prediction of key conformations and has identified additional residues critical for voltage sensing.